Pārasī komanī hālanī hālata tenī behatarī māṭe agatyanī yojanā - Banājī, Bahamana Śorābajī Jahāṃ (Jāme Jamśeda Prīṇṭīṅga Varkasa, 1911)
Status of Parsee community in India and a plan for their upliftment.